Zachowania ryzykowne młodych ludzi – wybrane problemy i wyzwania - Pawełek , Katarzyna (Studia Edukacyjne, 2019)
Research shows that although most children violate important behavioral norms at some point in time, it is possible to distinguish among them those who do so more intensely, engaging in physical and verbal aggression, abusing drugs, cigarettes and alcohol, stealing, committing acts of vandalism or failing to follow the rules set by adults. Not all of these behaviors are identified in time by the institutions of formal and informal social control, thus giving ground for their escalation. These behaviors, taking different form and level of representiality, disturb school order. The article refers to the data relating to the situation in American schools in the last decade of the 20th century and the two decades of the 21st century, and to the results of international surveys, which indicate a drop in the age of young people engaging in risky behaviour. Attention was also paid to changes in teenagers’ everyday activities, criminalization and the medicalisation of school discipline.